Dimensional stability, fire performance and decay resistance in wood impregnated with Alkylalkoxysilanes - Canosa, Guadalupe (2013)
The wood, very heterogeneous and complex material, changes its volume by water absorption or desorption causing swelling or shrinkage and also it can be degraded both by action of microorganisms and fire; the above-mentioned is a great inconvenient for most commercial uses. In this research, wood specimens of Pinus radiata were previously pretreated in a Soxhlet extractor for 2 hours with a solution of sodium hydroxide (activation of the cellulose) and then impregnated with alkylalkoxysilanes hydrolyzed and condensed "in situ" by the sol-gel process. Silanes selected were triethoxysilane, methyltriethoxysilane, n-propyltriethoxysilane, n-buthyltriethoxysilane and n-octhyltriethoxysilane. Impregnation process was carried out under controlled operating conditions to achieve similar weight gains of the chemical modifier. The pH was adjusted to alkaline value for controlling kinetic of hydrolysis and condensation reactions. Results indicated that dimensional stability increased with the increase of the length of the hydrocarbon chain of the alkoxydes, which would be based essentially on their enhanced hydrophobicity but without discarding the partial occupation of the pores by polymerized siloxanes and the interaction of alkoxides with cell wall components. In addition, wood specimens impregnated with mentioned alkylalkoxysilanes also showed an excellent fire performance and decay resistance.